Design of monolithic closed-cell polymer foams via controlled gas-foaming for high-performance solar-driven interfacial evaporation. Issue 15 (6th April 2021) - Qiao, Lifang; Li, Na; Luo, Lin; He, Jintao; Lin, Yuxuan; Li, Jingjing; Yu, Liangmin; Guo, Cui; Murto, Petri; Xu, Xiaofeng
Abstract : A monolithic 3D interfacial steam generator is successfully constructed via a controlled gas-foaming technique and demonstrated for high-performance solar evaporation and desalination under a variety of realistic conditions. Abstract : Solar-driven interfacial evaporation has emerged as an innovative and sustainable technology for clean water production. The rational fabrication of monolithic three-dimensional (3D) steam generators has accordingly become a topic of growing interest. However, the existing porous and hydrophilic 3D scaffolds (aerogels, hydrogels and sponges/foams) are constructed via conventional processing techniques (sol–gel and template-assisted methods), which remain one of the main roadblocks toward mass and large-scale applications. Herein, a closed-cell 3D polymer foam is developed via a controlled gas-foaming technique and applied as a monolithic interfacial steam generator for the first time. Taking advantage of the numerous gas pockets separated by reticulated and hydrophilic nanofibers that are made from polymeric composites, the foam has ultralight weight, low thermal conductivity and efficient water diffusion. Gratifyingly, the device attains a high water evaporation rate of 2.7 kg m −2 h −1 under one sun and is among the best-performing interfacial steam generators reported to date and surpasses a majority of 3D sponges/foams used in solar evaporation applications. This work demonstrates one of the few interfacial steam generators that integrate a variety of intriguing properties ( i.e., self-floating, light-to-heat conversion, structural durability, anti-overturning and anti-biofouling) into a monolithic polymer foam for high-performance solar evaporation in natural environments.